2016
DOI: 10.1007/s10995-016-2175-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Access to Medical Lactation Support and Counseling: Building the Case for Medicaid Reimbursement

Abstract: Objectives While the Affordable Care Act improves access to lactation services for many women across the US, low-income mothers in states without Medicaid expansion lack coverage for lactation support. As these states consider individual Medicaid reimbursement policies, the availability, effectiveness, and cost-benefit of lactation services must be evaluated. We conducted such an analysis for low-income mothers in North Carolina (NC), providing a model for other states. Methods First, we analyzed the distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…While breastfeeding rates in the Southeast are lower compared with other regions of the United States, breastfeeding rates in North Carolina are the highest in this region, with approximately 85% of women ever breastfeeding and 27% exclusively breastfeeding at six months (Centers for Disease Control and Prevention, 2018). Women living near Chapel Hill have been found to have greater access to Baby-Friendly Hospitals and IBCLCs compared with women in other areas of the state (Liberty, Wouk, Chetwynd, & Ringel-Kulka, 2019;Wouk, Chetwynd, Vitaglione, & Sullivan, 2016). Women were recruited for this study from study fliers and obstetric or psychiatric visits at clinics affiliated with the University of North Carolina Hospital, a Baby-Friendly hospital, between May 2013 through April 2017.…”
Section: Settingmentioning
confidence: 99%
“…While breastfeeding rates in the Southeast are lower compared with other regions of the United States, breastfeeding rates in North Carolina are the highest in this region, with approximately 85% of women ever breastfeeding and 27% exclusively breastfeeding at six months (Centers for Disease Control and Prevention, 2018). Women living near Chapel Hill have been found to have greater access to Baby-Friendly Hospitals and IBCLCs compared with women in other areas of the state (Liberty, Wouk, Chetwynd, & Ringel-Kulka, 2019;Wouk, Chetwynd, Vitaglione, & Sullivan, 2016). Women were recruited for this study from study fliers and obstetric or psychiatric visits at clinics affiliated with the University of North Carolina Hospital, a Baby-Friendly hospital, between May 2013 through April 2017.…”
Section: Settingmentioning
confidence: 99%
“…Grubesic and Durbin (2016) similarly reported a positive association between IBCLCs per capita and county-level breastfeeding initiation rates in the state of Kentucky. Wouk, Chetwynd, Vitaglione, and Sullivan (2017) found that that a higher density of IBCLCs was associated with higher breastfeeding rates at 6 weeks in North Carolina. These correlations in cross-sectional analyses are not proof of causation-increased proximity and density of IBCLCs may be associated with higher breastfeeding rates due to higher community socioeconomic status or more breastfeeding-friendly medical communities.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, mothers in low-income populations experience shorter maternity leaves and inflexible employment environments, which ultimately shorten breastfeeding duration (US Department of Health and Human Services, 2011). This effect is especially true for women experiencing high psychosocial distress (Guendelman et al, 2009) and for those who lack lactation support (Wouk et al, 2017). For women, factors that are associated with higher levels of breastfeeding include whether the mother was breastfed herself (Dunn et al, 2015), whether the father of the infant is supportive of breastfeeding (Alexander et al, 2010b) and availability of lactation support (Wouk et al, 2017).…”
Section: Breastfeeding In Low-income Populationsmentioning
confidence: 99%
“…This effect is especially true for women experiencing high psychosocial distress (Guendelman et al, 2009) and for those who lack lactation support (Wouk et al, 2017). For women, factors that are associated with higher levels of breastfeeding include whether the mother was breastfed herself (Dunn et al, 2015), whether the father of the infant is supportive of breastfeeding (Alexander et al, 2010b) and availability of lactation support (Wouk et al, 2017). Lack of education about the benefits of breastfeeding is another possible contributor to low breastfeeding rates in low-income populations.…”
Section: Breastfeeding In Low-income Populationsmentioning
confidence: 99%